Fingolimod Potentiates the Antifungal Activity of Amphotericin B - Wei, Lu-Qi; Tan, Jing-Cong; Wang, Yue; Mei, Yi-Kun; Xue, Jia-Yu; Tian, Lei; Song, Ke-Yu; Han, Lu; Cui, Ying-Chao; Peng, Yi-Bing; Li, Jing-Quan; Liu, Ning-Ning; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Candida albicans, the opportunistic human fungal pathogen, can contribute to occurrence and development of IBD. Its incidence and mortality rate has been increasing rapidly. Amphotericin B, the clinical gold standard antifungal agent, has a severe side effect which limits its clinical application. Thus, lowering the concentration and increasing the efficacy of amphotericin B by a combinatorial antifungal was pursued by both industry and academy. Here we identified that fingolimod, an immunomodulatory drug used for oral treatment of relapsing-remitting multiple sclerosis, can potentiate the efficacy of amphotericin B against Candida albicans growth synergistically. Furthermore, we observed a broad-spectrum antifungal efficacy against diverse fungal pathogens. Intriguingly, cells treated with both drugs were hypersensitive to endothelial endocytosis and macrophage killing. This was later found to be due to the hyperaccumulation of reactive oxygen species and the accordingly increased activities of superoxide dismutase and catalase in the cells that received combinatorial treatment. Therefore, the combination of amphotericin B and fingolimod provides a promising antifungal strategy.